2020
DOI: 10.1371/journal.pmed.1003228
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery for patients with type 2 diabetes mellitus requiring insulin: Clinical outcome and cost-effectiveness analyses

Abstract: Background Although bariatric surgery is well established as an effective treatment for patients with obesity and type 2 diabetes mellitus (T2DM), there exists reluctance to increase its availability for patients with severe T2DM. The aims of this study were to examine the impact of bariatric surgery on T2DM resolution in patients with obesity and T2DM requiring insulin (T2DM-Ins) using data from a national database and to develop a health economic model to evaluate the cost-effectiveness of surgery in this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Thirty original articles from 33 publications fulfilled the inclusion criteria. Of these, 16 reported on the cost-effectiveness of metabolic surgery specifically in a T2D population [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], including two empirical studybased economic evaluations [34,40]. Seventeen publications reported on the cost-effectiveness of metabolic surgery in a population with obesity in which a subgroup of the population had T2D [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty original articles from 33 publications fulfilled the inclusion criteria. Of these, 16 reported on the cost-effectiveness of metabolic surgery specifically in a T2D population [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], including two empirical studybased economic evaluations [34,40]. Seventeen publications reported on the cost-effectiveness of metabolic surgery in a population with obesity in which a subgroup of the population had T2D [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Search Resultsmentioning
confidence: 99%
“…Of 14 model-based economic evaluations conducted specifically in a population with T2D, eight considered a mix of metabolic surgery procedures, typically reflective of clinical practice in the reference country (Supplementary Information, Table S4) [27,28,30,31,35,36,38,39]. Six studies considered RYGB or adjustable gastric banding (AGB) only [29,32,33,37,41,42].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Diabetic cardiomyopathy is a pivotal cause of morbidity and mortality in patients with T2DM, and is defined by morphological, functional, and metabolic transformations in the heart as a significant cardiovascular complication in diabetic patients ( Adeghate and Singh, 2014 ; Bugger and Abel, 2014 ). Ample evidence has showed that bariatric surgery had significant metabolic advantages in obesity, T2DM, and following complications ( Ikramuddin et al, 2018 ; McGlone et al, 2020 ). In the present study, we induced DCM rat models by HFD feeding followed with low-dose intraperitoneal injection of STZ.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery has remarkable metabolic benefits in obesity, T2DM, and following complications [ 6 , 28 , 29 ]. In the present study, we found that SG surgery alleviated the capability of myocardial contraction and diastole and delayed the progression of DCM.…”
Section: Discussionmentioning
confidence: 99%